Paced breathing in roller-ski skating: Effects on metabolic rate and poling forces - Fabre, N.; Perrey, S.; Arbez, L.; Rouillon, J. D. (International Journal of Sports Physiology and Performance, 2007)
This study aimed (1) to determine whether paced breathing (synchronization of the expiration phase with poling time) would reduce the metabolic rate and dictate a lower rate of perceived exertion (RPE) than does spontaneous breathing and (2) to analyze the effects of paced breathing on poling forces and stride-mechanics organization during roller-ski skating exercises. Methods: Thirteen well-trained cross-country skiers performed 8 submaximal roller-skiing exercises on a motorized driven treadmill with 4 modes of skiing (2 skating techniques, V2 and V2A, at 2 exercise intensities) by using 2 patterns of breathing (unconscious vs conscious). Poling forces and stride-mechanics organization were measured with a transducer mounted in ski poles. Oxygen uptake (VO2) was continuously collected. After each bout of exercise RPE was assessed by the subject. Results: No difference was observed for VO2 between spontaneous and paced breathing conditions, although RPE was lower with paced breathing (P < .05). Upper-limb cycle time and recovery time were significantly (P < .05) increased by paced breathing during V2A regardless of the exercise intensity, but no changes for poling time were observed. A slight trend of increased peak force with paced breathing was observed (P = .055). Conclusion: The lack of a marked effect of paced breathing on VO2 and some biomechanical variables could be explained by the extensive experience of our subjects in cross-country skiing.